Implemetasi Syariat Islam Dalam Mewujudkan Keluarga Sakinah (Studi Kasus Masyarakat di Kecamatan Danau Teluk Seberang Kota Jambi) - Maryani Maryani (Al-Risalah, 2011)
The sub-district of danau seberang kota jambi is located in kota jambi, the province of jambi. This area is wellknown with its’ people who are religious and respect the local culture there is saying here adat bersendi syara’ sara’ bersendikan kitabullah sara’ mengato aat memakai, sara’ mendaki adat menurun”. The research is aimed at investigation on how to build a good family in the people of danau teluk seberang kota jambi is categorized into fair family, good family 1, good family 2, good family 3, good family 3 plus/ 4. Besides that, the writer wants to study particulary the applications of Islamic principles, especially to the citizens of ulu gedong dan olak kemang in sub-district danau teluk kota seberang jambi. The result of the research shows that people already implement the Islamic principles in building a good family, for example by doing the five-time-a day praying, praying together, rembering god, and praying in happy and sorrow contion, and others. The efforts to build a good family between husband and wife trough : accepting the preality adapt each other foster the love , and so furth, the people of sub-distruct danau teluk kota seberang kota jambi is cotagarized into “good family” which is: a family that build based on legal marriage, affwction do five-times a-day praying do fasting pay the obligatory-donation learn the basic of religion and there is place to live the quality of marriage increases when the household applies religion principles. The religion will be the foundation for good activities and prevent from bad habits or actions. If husband and wife always do what Islam asks to do, as the effect, every problem in a family can be solved. Thus, the real quality of a good family will come true.